Evaluation of dihydroquercetin-3-O-glucoside from Malbec grapes as copigment of malvidin-3-O-glucoside - Fanzone, Martín Leandro; González-Manzano, Susana; Pérez-Alonso, Joaquín; Escribano-Bailón, María Teresa; Jofre, Viviana Patricia; Assof, Mariela Vanesa; Santos-Buelga, Celestino (2018)
Malbec is a wine grape variety of great phenolic potential characterized for its high levels of anthocyanins and dihydroflavonols. To evaluate the possible implication of dihydroflavonols in the expression of red wine color through reactions of copigmentation or condensation, assays were carried out in wine model systems with different malvidin-3-O-glucoside:dihydroquercetin-3-O-glucoside molar ratios. The addition of increasing levels of dihydroquercetin-3-O-glucoside to a constant malvidin-3-O-glucoside concentration resulted in a hyperchromic effect associated with a darkening of the anthocyanin solutions, greater quantity of color and visual saturation, perceptible to the human eye. Copigmentation and thermodynamic measurements showed that dihydroquercetin-3-O-glucoside can act as an anthocyanin copigment, similar to other usual wine components like flavanols or phenolic acids, although apparently less efficient than flavonols. The high levels of dihydroflavonols existing in Malbec wines in relation to other non-anthocyanin phenolics should make this family of compounds particularly important to explain the color expression in Malbec young red wines.